Cognitive assistants - An analysis and future trends based on speculative default reasoning - Ramos, João (2018)
Once a person is diagnosed (or a caregiver suspects that the person may have) cognitive disabilities he may lose the state of being autonomous, which may range from partial to total loss of independence, according to the level of incidence. Smart houses may be used as a tentative solution to overcome this situation. However, when one goes outside their premises, this alternative may become unusable. Indeed, due to the decreased orientation ability, caregivers may prevent these people from going out, as they may get lost. Therefore, we are developing a system for people with mild or moderate cognitive disabilities that guides the user through an augmented reality interface and provides a localization tool for caregivers. The orientation method implements a speculative computation module, thus the system may calculate and anticipate possible user mistakes and issue alerts before he takes the wrong path. Through a trajectory mining module, the path is also adjusted to user preferences. These two modules enable the system to adapt to the user.